Evaluation of rapid detection kit against avian influenza A virus and H5 subtype for field Sample - Michael Haryadi Wibowo; Tri Untari; Sidna Artanto; Krisdiana Putri; Surya Amanu; Widya Asmara (Universitas Gadjah Mada, 2016)
Avian influenza virus is poultry viral disease, which causes high economic losses. Various efforts have been made to control the disease. One effort is required screening fast and precise diagnostic test. This study was aimed to determine the potential of rapid test kit of AIV/H5 Anigen Rapid Test for the detection of AI virus types A and subtype H5 in the field. Some tests were carried out, e.g.: the potential test, cross-reaction test, sensitivity and specificity test. Potency test was done to evaluate potential of detection limits of the kit, by having the test of serial dilution of AI virus positive control. Cross-reaction test was done to detect antigens other than AI virus H5N1, e.g.: IB virus of Massachuset strain, IBV strain 4-91, Newcastle Disease virus, and Escherichia coli. Sensitivity and specificity test were applied to the filed samples which clinically and laboratory were confirmed as H5N1 positive. To confirm the result of rapid test was then being done by reverse transcriptase polymerase chain reaction. Based on these results it can be concluded that, Anigen Kit AIV/H5 Ag Rapid Test can detect antigen-containing samples having AI virus HA titer up to 26of type A virus, and up to 25 for subtype H5 virus. Anigen Kit AIV/H5 Ag Rapid Test showed no cross-reactions with Infectious Bronchitis virus, Newcastle Disease virus, and Escherichia coli. Anigen A Rapid Test Kit AIV Ag showed a sensitivity of 50% and specificity of 100%, while Anigen Ag Rapid Test Kit AIV/H5 showed a sensitivity of 25% and specificity is 100%.